Aksi Kolektif Mengibarkan Bendera Putih Oleh Pedagang Kuliner di Malioboro Atas Diterapkannya PPKM Darurat (Jurnal Nawala Politika, 2023)
In dealing with spread of the Covid-19 outbreak in Indonesia, Indonesian government enforced a policy of Restrictions on Community Activities (Emergecy PPKM). This policy impacted the economic decline of Indonesian people significantly. A month after PPKM was implemented, several culinary vendors in Malioboro raised white flags as a way to knock Yogyakarta governmen’s heart for help. The purpose of this study is to find out the result of the collective action of raising the white flags carried out by culinary vendors in Malioboro. This study uses descriptive qualitative research methods and studied by Neil J. Smelser's theory of collective action. The result of this research is the act of raising white flags in Malioboro was just collective action not a resistance movement of vendors in Malioboro to Yogyakarta government. The impact received by traders is basic food assistance from various parties and other assistance after the collective action carried out.